2022
DOI: 10.2166/wh.2022.230
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pathogenic microorganisms in small drinking-water systems in Costa Rica

Abstract: This study describes the quality of drinking water sampled over 2 years (2018 and 2019) from 20 ASADAS (Spanish acronym for Administrative Associations for Water and Sewer Systems) in Costa Rica. The analysis included Rotavirus (RV), somatic coliphages, fecal coliforms, and Escherichia coli. The ASADAS were categorized into three regions as temperate rainy (region 1), tropical rainy (region 2), and tropical rainy and dry (region 3) according to biogeographic classification. The concentrations of fecal coliform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…For this reason, E. coli is an accurate indicator of fecal contamination due to its constant presence in the intestine and feces of warm-blooded animals. The presence of TtC in any body of water has a high predictive value for the potential presence of other pathogenic microorganisms for humans [19][20][21]30 . On the other hand, it has been suggested that the presence of IE might be used as a supplementary test for assessing water quality.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, E. coli is an accurate indicator of fecal contamination due to its constant presence in the intestine and feces of warm-blooded animals. The presence of TtC in any body of water has a high predictive value for the potential presence of other pathogenic microorganisms for humans [19][20][21]30 . On the other hand, it has been suggested that the presence of IE might be used as a supplementary test for assessing water quality.…”
Section: Resultsmentioning
confidence: 99%
“…RV has been detected in perishable foods for consumption such as shellfish and vegetables in countries like Mexico, where this virus has been detected together with other viruses such as norovirus and hepatitis [13]. RV detection studies have been carried out in drinking water for consumption in the Central Valley of Costa Rica, where the presence of RV has been identified [38]. In Leon, Nicaragua, RV was identified in wastewater, in low prevalence, after vaccination [25].…”
Section: Rotavirus Detected In Food and Water In Latin Americamentioning
confidence: 99%
“…Disposal of liquid waste that does not meet the requirements can cause contamination of groundwater surfaces and water sources. According to (Barrantes et al, 2022), rotavirus, enterovirus, and norovirus are pathogens that are often transmitted through water. They pollute water through human activities such as leakage of sewers and septic systems, agricultural and urban runoff, and unsafe disposal of wastewater.…”
Section: Variablesmentioning
confidence: 99%